2007
DOI: 10.1016/j.icarus.2007.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Martian water vapor: Mars Express PFS/LW observations

Abstract: We present the seasonal and geographical variations of the Martian water vapor monitored from the Planetary Fourier Spectrometer Long Wavelength Channel aboard the Mars Express spacecraft. Our dataset covers one Martian year (end of Mars Year 26, Mars Year 27), but the seasonal coverage is far from complete. The seasonal and latitudinal behavior of the water vapor is globally consistent with previous datasets, Viking Orbiter Mars Atmospheric Water Detectors (MAWD) and Mars Global Surveyor Thermal Emission Spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
103
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 108 publications
(116 citation statements)
references
References 59 publications
13
103
0
Order By: Relevance
“…Seasonal water reservoirs include water ice on or within the seasonal or residual polar caps, surface or subsurface ice in high-latitude regions, physically adsorbed and chemically-bound water within the near-surface regolith, and possibly surface and subsurface liquid water in the form of liquid saline solutions (brine) (Jakosky 1985). Satellite and telescopic observations of variations in the integrated H 2 O column abundance (Conrath et al 1973;Jakosky and Farmer 1982;Sprague et al 1996;Smith 2004;Fedorova et al 2006;Fouchet et al 2007;Melchiorri et al 2006), in combination with numerical modeling, have been used to determine the relative importance of the various processes controlling the seasonal H 2 O cycle (Flasar and Goody 1976;Jakosky and Farmer 1982;Haberle and Jakosky 1990;Richardson and Wilson 2002;Böttger et al 2005). The seasonal H 2 O cycle is important for the Martian climate because it leads to the formation and affects the stability of water ice deposits on the surface and of water ice clouds in the atmosphere (Jakosky and Haberle 1992;Richardson and Wilson 2002;Smith et al 1997;Haberle et al 1999;Montmessin et al 2004;Madeleine et al 2012).…”
Section: Figmentioning
confidence: 99%
“…Seasonal water reservoirs include water ice on or within the seasonal or residual polar caps, surface or subsurface ice in high-latitude regions, physically adsorbed and chemically-bound water within the near-surface regolith, and possibly surface and subsurface liquid water in the form of liquid saline solutions (brine) (Jakosky 1985). Satellite and telescopic observations of variations in the integrated H 2 O column abundance (Conrath et al 1973;Jakosky and Farmer 1982;Sprague et al 1996;Smith 2004;Fedorova et al 2006;Fouchet et al 2007;Melchiorri et al 2006), in combination with numerical modeling, have been used to determine the relative importance of the various processes controlling the seasonal H 2 O cycle (Flasar and Goody 1976;Jakosky and Farmer 1982;Haberle and Jakosky 1990;Richardson and Wilson 2002;Böttger et al 2005). The seasonal H 2 O cycle is important for the Martian climate because it leads to the formation and affects the stability of water ice deposits on the surface and of water ice clouds in the atmosphere (Jakosky and Haberle 1992;Richardson and Wilson 2002;Smith et al 1997;Haberle et al 1999;Montmessin et al 2004;Madeleine et al 2012).…”
Section: Figmentioning
confidence: 99%
“…However this assumption may be incorrect, due to possible fractionation effects associated to water condensation and sublimation (Fouchet & Lellouch 2007) or photodissociation. Montmessin et al (2005) have calculated the expected D/H ratio on Mars as a function of latitude and season.…”
Section: Retrieval Of the Water Vapor Mixing Ratiomentioning
confidence: 99%
“…Mars Express instruments disagree whether the watervapor mixing ratio stays constant from the bottom to the top of the volcano. Using PFS/LW data, Fouchet et al (2007) found the H 2 O mixing ratio to be constant within a factor 2 over Olympus Mons, while Maltagliati et al (2006Maltagliati et al ( , 2008 used OMEGA data to find some spatial and temporal variabilities with, in most of the cases, a local enhancement of the water mixing ratio by a factor of 4 around the summits. Assuming a conservative maximum possible enhancement by a factor of 4 in the mixing ratio over Olympus Mons, the resulting water-vapor column density would be 6.4 pr-µm instead of 1.6 pr-µm.…”
Section: Omegamentioning
confidence: 99%
“…The PFS long-wavelength data were used in the thermal regime (Fouchet et al 2007), while both the OMEGA and SPICAM analyses were based on the reflected part of the spectrum. The OMEGA analysis used the H 2 O 2.6-µm band (Encrenaz et al 2005;Melchiorri et al 2007a;Maltagliati et al 2007), and the SPICAM results were obtained from the 1.38-µm water band (Fedorova et al 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation